Book lending information system design - Wahyu Hidayah; Agus Sulistyanto; Asih Septia Rini; Rumadi Hartawan (Yayasan Bina Internusa Mabarindo, 2022)
Currently, the process of data processing on borrowing books at the SMA 1 Muhammadiyah Jakarta Library is still done semi-computerized, namely using manual systems such as borrowing notebook media in recording transaction reports on borrowing/returning books at the SMA 1 Muhammadiyah Jakarta library. This of course allows for human error and other risks that will be problematic if continued. In overcoming the problem, the researcher proposes to design an information system for borrowing library books at SMA 1 Muhammadiyah Jakarta which is expected to help the library management in terms of data management for the better. To build a system, here the author uses the Waterfall method, for system modeling using UML (Unifield Modeling Language) and the software used in building the system by using the PHP and XAMPP programming languages ​​as connections to the database, namely MySQL. The data collection method used was observation, interviews and literature. It is hoped that the existence of a Book Borrowing Information System at the SMA 1 Muhammadiyah Jakarta Library can help facilitate the transaction process of data processing borrowing/returning books to be more effective and efficient